Cell Death and Survival Through the Endoplasmic Reticulum- Mitochondrial Axis - Bravo-Sagua, R.; E. Rodriguez, A.; Kuzmicic, J.; Gutierrez, T.; Lopez-Crisosto, C.; Quiroga, C.; Diaz-Elizondo, J.; Chiong, M.; G. Gillette, T.; A. Rothermel, B.; Lavandero, S. (Current Molecular Medicine, 2013)
The endoplasmic reticulum has a central role in biosynthesis of a variety of proteins and lipids. Mitochondria generate ATP, synthesize and process numerous metabolites, and are key regulators of cell death. The architectures of endoplasmic reticulum and mitochondria change continually via the process of membrane fusion, fission, elongation, degradation, and renewal. These structural changes correlate with important changes in organellar function. Both organelles are capable of moving along the cytoskeleton, thus changing their cellular distribution. Numerous studies have demonstrated coordination and communication between mitochondria and endoplasmic reticulum. A focal point for these interactions is a zone of close contact between them known as the mitochondrial-associated endoplasmic reticulum membrane (MAM), which serves as a signaling juncture that facilitates calcium and lipid transfer between organelles. Here we review the emerging data on how communication between endoplasmic reticulum and mitochondria can modulate organelle function and determine cellular fate.
Keywords: ceramides